Microbial decontamination of particulate food using a pilot-scale atmospheric plasma jet treatment system. (April 2021) - Lee, Seung Young; In, Jiwon; Chung, Myong-Soo; Min, Sea C.
Abstract: A pilot-scale treatment system of atmospheric plasma jet (APJ) was developed and its effects on the inactivation of natural bacteria in rice germ, black pepper powder, and sesame were investigated. The optimal sample amount, rotary valve speed, operation time, and plasma jet pressure for inactivation were determined to be 200 g, 40 rpm, 10 min, and 0.2 MPa, respectively, which inactivated natural bacteria in rice germ, black pepper powder, and sesame by 1.4, 1.0, and 1.4 log CFU/g, respectively. Dust removal pre-treatment increased the microbial reduction level in sesame by 2.2 log CFU/g. Plasma treatment did not alter the color of rice germ and sesame and the antioxidant activities of black pepper powder and sesame. The plasma jet treatment system consumed 1.6 times less energy than conventional heat treatment. The results demonstrated the potential of using the pilot-scale APJ system for microbial disinfection of particulate food. Highlights: Pilot-scale atmospheric plasma jet is effective in decontaminating particulate food. Bacterial reduction varies with sample amount, valve speed, and operation time. Dust removal before plasma treatment increases bacterial reduction levels on sesame. Pilot-scale plasma jet disinfects particulate food without affecting food quality.